Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s11064-005-9011-9
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution and Neurochemistry of the Parathyroid Hormone 2 Receptor in the Rat Hypothalamus

Abstract: This study reports the distribution of parathyroid hormone 2 receptor (PTH2R)-immunoreactive fibers in the hypothalamus using fluorescent amplification immunocytochemistry. The pattern of immunolabeling is strikingly similar to that of tuberoinfundibular peptide of 39 residues (TIP39), a peptide recently purified from bovine hypothalamus and proposed to be a ligand of the PTH2R based on pharmacological data. To investigate the anatomical basis of suggestions that TIP39 affects the secretion of several hypophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 30 publications
4
50
0
3
Order By: Relevance
“…In several brain regions, PTH2Rs have been shown to be located on glutamatergic nerve terminals (11,19). We found that this colocalization is also the case in the LC area.…”
Section: Resultssupporting
confidence: 65%
“…In several brain regions, PTH2Rs have been shown to be located on glutamatergic nerve terminals (11,19). We found that this colocalization is also the case in the LC area.…”
Section: Resultssupporting
confidence: 65%
“…Every fourth free-floating section was first stained for TIP39 using FITC-tyramide amplification fluorescent immunocytochemistry. An affinity-purified antiserum from a rabbit immunized with rat TIP39, which can be absorbed with synthetic TIP39 (Dobolyi et al 2002), and labels cell bodies with the same distribution as observed by in situ hybridization histochemistry (Dobolyi et al 2006a, b), was used as primary antiserum. This antiserum (1:3000) was applied for 48 h at room temperature, followed by incubation of the sections in biotinylated donkey anti-rabbit secondary antibody (1:1000; Jackson ImmunoResearch), then in ABC complex (1:500; Vector Laboratories) for 2 h. Sections were subsequently incubated with FITC-tyramide (1:8000) and H 2 O 2 in Tris hydrochloride buffer (0.1 M, pH 8.0) for 6 min.…”
Section: Methodsmentioning
confidence: 99%
“…Free-floating sections were then pretreated with 1% bovine serum albumin in PBS containing 0.6% Triton X-100 for 30 min at room temperature. The sections were then placed in anti-TIP39 primary antiserum (1:3000 for tyramide amplification and 1:600 for DAB reaction) for 48 hours at room temperature or anti-PTH2 receptor primary antiserum (1:60000 for tyramide amplification and 1:15000 for DAB reaction) for 24 hours at room temperature as described previously (Dobolyi et al, 2006;Usdin et al, 1999a;Usdin et al, 1999b;Wang et al, 2000). The sections were then incubated in biotinylated anti-rabbit secondary antibody (1:600 dilution; Vector Laboratories, Burlingame, CA) for 2 hours followed by incubation in a solution containing avidin-biotin-peroxidase complex (1:150; Vector Laboratories, Burlingame, CA) for 2 hours.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…The distributions of TIP39 fibers (Dobolyi et al, 2003b) and the PTH2 receptor in the central nervous system have recently been described in young male rats. PTH2 receptors and TIP39 fibers have similar distributions in many brain regions, suggesting that they form a neuromodulator system (Dobolyi et al, 2006). TIP39 fibers and PTH2 receptors are abundant in the medial prefrontal cortex, the lateral septum, the amygdala, several different hypothalamic nuclei, the paraventricular thalamic nucleus, and the parabrachial nuclei (Dobolyi et al, 2006;Dobolyi et al, 2003b;Wang et al, 2000) suggesting limbic-endocrine functions for TIP39 (Dobolyi et al, 2003a;Usdin et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation